Challenges in Qur’anic Memorization Learning at Elementary Schools: Systematic Literature Review - Nasiruddin Al Arifi; Zurqoni Zurqoni; Robingatin Robingatin (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Qur'anic memorization has become a central component of Islamic education in many elementary schools across Muslim-majority countries; However, its implementation still faces pedagogical and institutional challenges that hinder its effectiveness. This study aims to address this gap by systematically identifying and synthesizing research on the challenges and solutions in Qur'anic memorization learning at the elementary school level. Employing a Systematic Literature Review (SLR) based on PRISMA guidelines, literature was retrieved from Scopus, covering publications between 2015 and 2025, with fourteen studies meeting the inclusion criteria. The findings reveal four main categories of challenges: (1) student-related factors (cognitive limitations, psychological fatigue, motivation issues), (2) teacher-related factors (limited pedagogical skills, lack of standardization), (3) curriculum and time management issues (balancing memorization with general education), and (4) institutional barriers (limited resources, weak monitoring, and policy gaps). The discussion emphasizes that effective solutions require pedagogical innovation, technology integration, teacher professional development, and stronger collaboration among schools, parents, and policymakers. These findings provide valuable implications for educators and curriculum developers in designing holistic and sustainable Qur'anic memorization programs for young learners.